PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN CENGKARENG JAKARTA BARAT - Sazly, Syukron; Ardiani, Yolanda (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
Abstract-Good management will facilitate the realization of the objectives of agencies, employees, and the community. With usability management and results of use the elements of management will be improved. In achieving agency goals many elements are important in fulfilling them, including elements of leadership or leaders. Resources that are available if not managed properly will not get the planned goals so that the role of leaders is very important that can use authority and leadership to achieve a goal. In this case, Transformational Leadership is the key, because this transformationalleadership will be able to change the value shared to employees to be excellent output. The method of data collection in this research are observations, interviews, documentation studies, and questionnaires from 44 respondents with purposive sampling technique . We use SPSS 22 software to process all data gained from the survey.The research was held at Januari 2019 till March 2019 . The research shows that , the correlation test is medium correlated( r=0.586), caused exists at interval of 0,400-0,599. From regression analysis, there is a low  influence of  transformational leadership  to the performance just at   34,4% and the rest, 65,6% influenced by other factors. So, based on the results of the regression test can be concluded that the transformational leadership  have a low effect on employee performance working at the office of Kecamatan Cengkareng,  Jakarta Barat. Keywords: Transformational Leadership, Employee Performance